The Oil Curse Validated: Evidence from Eurasia and Latin America - Algharabali, Barrak; Butler, J. S.; Closson, Stacy (International Journal of Energy Economics and Policy, 2021)
Many studies have found a negative relationship between oil abundance and democracy. However, recent studies have tried to upend this correlation by employing time-series techniques or finding a conditionality on other factors. This study contributes to the literature by employing an Arellano Bond model that corrects for fixed effects and adopts new variables from recent empirical studies. Comparing Eurasia and Latin America from the 1960s to 2010, we find that the theory of a negative relationship between an abundance of natural resources and democracy remains valid. Keywords: natural resource curse, natural resource dependence, democracy, natural resource abundance JEL Classifications: N50, H6, P28 DOI: https://doi.org/10.32479/ijeep.10772